Pembelajaran aktif untuk meningkatkan pembelajaran mandiri di antara guru siswa - Suroto, Suroto; Tjahyo Kuntjoro, Bambang Ferianto; Dinata, Vega Candra; Prakoso, Bayu Budi (Universitas Nusantara PGRI Kediri, 2022)
PETE, as a place for PE teacher training, requires an analysis of the functioning of subjects related to the SDGs. Since 2006, Active Learning Models (ALM) in track and field courses have aspired to provide contextual learning experiences to PE teacher candidates. However, there is no in-depth analysis of ALM implementation in ensuring the readiness and independence of student learning during lectures. The purpose of this study is to strengthen the evidence that ALM can build the self-regulation and self-efficacy of prospective PE teachers. This research is a weak experimental type using a one-shot case study design. The sample involved 142 students(M= 83 and F= 59) who followed the ALM syntax for one semester. Portfolios and log-activity scores were used to measure self-regulation, while the Authentic Learning Self-Efficacy Scale (ALSS) questionnaire was used to measure Self-Efficacy. Data analysis used descriptive, correlation, ANOVA, and regression. The results showed that the students possessed adequate self-efficacy while participating in ALM. The differences in the characteristics of students based on the class that necessitated adjustments in the implementation of the instructional model were discussed. In addition, learning activity was determined as the most important variable in explaining student self-regulation in successfully achieving academic achievement.